Spatial Multidimensionalities in the Politics of Regions: Constituting the ‘Phantom Region’ of Central Germany - Baars, Roger; Schlottmann, Antje (ERDKUNDE, 2015)
This paper provides a new perspective on the multi-dimensional character of regions as ‘spatial phantoms’ and contributes to the ongoing debate on interconnected relational and territorial approaches to regional space (cf. Elden, 2005, 2009, 2010; Jonas 2012a, 2012b, 2013; Jones 2009; Murphy 2013; Painter 2010). Using the example of the Central German Metropolitan Region, we show that regional spatialities co-constituted by relational and territorial concepts simultaneously, leading to a multitude of spatialities-in-becoming. We argue that, ontologically, regions are multidimensional polysemic spaces and can be realised as spatial phantoms with contextually changing and fluid spatialities. Due to discursive practices of ‘Geography Making’ in the context of culture and politics, however, these regions frequently, but not always, appear as bounded territorial containers.